Enhancing climate services design and implementation through gender-responsive evaluation - Gumucio, Tatiana; Hansen, James; Carr, Edward R.; Huyer, Sophia; Chiputwa, Brian; Simelton, Elisabeth; Partey, Samuel T.; Schwager, Saroja (Frontiers Media, 2022)
Assessing and responding to gender inequalities, and promoting women's empowerment, can be critical to achieving the goals of climate services, such as improved climate resilience, productivity, food security and livelihoods. To this end, our paper seeks to provide guidance to rural climate service researchers, implementing organizations, and funders on gender-responsive evaluation of climate services, including key questions to be asked and appropriate methodology. We draw on case studies of rural climate services in Mali, Rwanda and Southeast Asia to illustrate how gender-responsive evaluations have framed and attempted to answer questions about climate information needs, access to information and support through group processes, and contribution of climate services to empowerment. Evaluation of how group participatory processes can enable women's and men's demand for weather and climate information can help close knowledge gaps on gender equity in access to climate services. Quantitative methods can rigorously identify changes in demand associated with varying interventions, but qualitative approaches may be necessary to help assess the nuances of participatory communication processes. Furthermore, evaluation of how women's and men's information needs differ according to their roles and responsibilities in distinct climate-sensitive decisions can help assess gender inequities in climate services use. Evaluation that critically considers the local normative and institutional environment influencing empowerment can help identify pathways for climate services to contribute to women's empowerment. Qualitative and mixed method methodologies can be helpful for assessing the normative and institutional changes upon which empowerment depends. Although evaluations are often conducted too late to inform the design of time-bound projects, they can contribute to improvements to climate services if results are shared widely, if implementers and funders consistently factor evidence and insights from prior evaluations into the design of new initiatives, and if ongoing climate service initiatives conduct preliminary evaluations regularly to support mid-course adjustments.